173k views
4 votes
Simplify each expression.

1) 7x - 9x
2) -2x - 7+ 8x - 10
3) 3 - 10x - 3-6x
4) 2m - 6+ m + 1
5) 10m - 8m
6) x - 4+x-5
7 4x + 5x
8) -x + 3 + 7x + 5

Simplify each expression. 1) 7x - 9x 2) -2x - 7+ 8x - 10 3) 3 - 10x - 3-6x 4) 2m - 6+ m-example-1

1 Answer

2 votes

Answer:

1) -2x

2) 6x - 17

3) -16x

4) 3m - 5

5) 2m

6) 2x - 9

7) 9x

8) 6x + 8

Explanation:

1) = x(7-9) = x(2) = 2x

2) x(-2+8) - 7 - 10 = x(6) - 17 = 6x - 17

3) x(-10-6) + 3 - 3 = x(-16) + 0 = 16x

4) m(2+1) - 6 + 1 = 3m - 5

5) m(10-8) = m(2) = 2m

6) x(1+1) - 5 - 4 = 2x - 9

7) x(4+5) = x(9) = 9x

8) x(7-1) + 3 + 5 = 6x + 8

User Skamazin
by
6.5k points